2 (×+1)-3 (2×-5) =7×-3
Soluções para a tarefa
Respondido por
0
Assunto: Expressao algébrica.
• sendo:
2 * (x + 1) - 3 * (2x - 5) = 7x - 3
• tire as parêntesis:
2x + 2 - 6x + 15 = 7x - 3
• os x de um lado e os numeros de outro:
2x - 6x - 7x = -3 - 2 - 15
• simplifique:
-11x = -20
• valor de x:
11x = 20
x = 20/11
Respondido por
0
Resposta: 20/11
Explicação passo-a-passo:
2(x+1)-3(2x-5)=7x-3
2x+2-6x+15=7x-3
2x-6x-7x=-3-2-15
-11x=-20 (-1)
11x=20
x=20/11
Perguntas interessantes
Matemática,
10 meses atrás
Biologia,
10 meses atrás
Matemática,
10 meses atrás
Física,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás